Sardinella alcyone n. sp., a new sardine (Teleostei: Clupeiformes: Clupeidae) from the northwestern Pacific Ocean - Hata, Harutaka; Motomura, Hiroyuki (Zootaxa, 2019)
The new sardine Sardinella alcyone n. sp. is described on the basis of 19 specimens collected from the Ryukyu Islands, Japan and southwestern Taiwan. The new species closely resembles Sardinella pacifica Hata & Motomura 2019, both species having lateral scales with centrally discontinuous striae, a dark spot on the dorsal-fin origin, the pelvic fin with 8 rays, deciduous body scales, and very similar numbers of prepelvic and postpelvic scutes, scale rows in the longitudinal series, and pseudobranchial filaments. However, the new species is distinguished from S. pacifica by having lower total gill-raker counts on the first, second, third and fourth gill arches, and on the posterior face of the third gill arch (99–112, 97–115, 79–98, 62–77, and 25–31, respectively, vs. 112–137, 112–148, 95–127, 78–106, and 30–43), and greater pectoral fin (20.7–23.4% SL vs. 18.2–20.8%), pelvic fin (11.9–13.1% SL vs. 10.3–11.9%), maxilla (10.8–12.4% SL vs. 9.3–10.9%), lower jaw (11.8–13.4% SL vs. 10.4–11.6%), and pre-anal-fin length (77.4–82.3% SL vs. 72.9–79.3%) proportions.